Envolvimento dos acadêmicos no ecossistema universitário empreendedor em uma universidade tecnológica - Barboza, Claudia Marli Oliveira (2021)
The debate about entrepreneurship in universities is recurrent and has become more intense in the last two decades. Teaching, research, entrepreneurship and extension, for some researchers, have constituted the main missions of universities. The university plays a central role in the entrepreneurial ecosystem as it is the main provider of scientific and technological knowledge, as well as professional training. The debate on technology transfer between universities and the productive system is not recent, but it is still relevant, because the transfer mechanisms depend on the entrepreneurial ecosystem and, particularly, on the entrepreneurial university ecosystem. Recent international surveys (LAHIKAINEN et al., 2018) show that involving academics in entrepreneurial processes is not automatic, as the presence of policies and organizational structures are not enough to promote academic entrepreneurship. Based on this issue, this study aims to analyze how academics are involved in the entrepreneurial university ecosystem of a technological university. Therefore, it was based on the concepts of entrepreneurial university, entrepreneurial university ecosystem and academic entrepreneurship. The object of study is the Entrepreneurial University Ecosystem of the Federal Technological University of Paraná – UTFPR. Methodologically, this research is qualitative and quantitative in nature, characterized by the use of descriptive and analytical objectives, whose technical procedures used were: bibliographic, documental and field research. As data collection technique, we used: document analysis, semi-structured questionnaire and basic descriptive statistical analysis for data processing. The main results show that UTFPR’s entrepreneurial university ecosystem is formalized through institutional policies and programs, in addition to instructional documents. It has a dedicated team to support activities that promote entrepreneurship and innovation. However, the entrepreneurial culture still needs to be put into effect. Most academics are unfamiliar with institutional values and policies. Most of the students want to undertake, however, they were not motivated or trained by UTFPR and believe that the courses are oriented towards training professionals who will be employed. For most professors, institutional policies are known, but they prefer teaching and research activities, extension, related to entrepreneurship, and technology transfer. Finally, the main challenges pointed out by academics for greater involvement in the entrepreneurial university ecosystem are access to financial resources to undertake and establishing partnerships, in addition to the challenge of identifying strategies to motivate students to get involved in entrepreneurship.